2019
DOI: 10.1037/emo0000412
|View full text |Cite
|
Sign up to set email alerts
|

Disgust and the sacred: Do people react to violations of the sacred with the same emotion they react to something putrid?

Abstract: Disgust has been hypothesized to be uniquely linked to violations of a distinct moral domain (called divinity, purity, or sacred) aimed at preserving one's body from contamination with pathogens and preserving one's soul from violations of what is sacred. Here we examined whether the same emotion-core disgust-occurs when witnessing both types of violation, and we proposed a specific method for doing so. In two studies (N = 160; 240), American and Indian participants indicated their emotional reaction to (stori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…A possible reason is that many of the purity violations in this study include pathogen-relevant content (e.g., syringe injection, smelling bad, surgery, eating in a bathroom; Oaten et al, 2018; Royzman, Atanasov, Landy, Parks, & Gepty, 2014), which could potentially evoke a canonical disgust expression relatively independently of the judged severity of the behavior itself. This would be consistent with recent findings that reactions to classic purity violations are distinctively associated with disgust sensitivity (e.g., Tracy, Steckler, & Heltzel, 2019; Wagemans, Brandt, & Zeelenberg, 2018) but also with concerns about whether the classic purity domain violations are tapping into moral intuitions about behavior or other issues (Gray & Keeney, 2015; Kollareth & Russell, 2019; Royzman et al, 2014; Uhlmann & Zhu, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…A possible reason is that many of the purity violations in this study include pathogen-relevant content (e.g., syringe injection, smelling bad, surgery, eating in a bathroom; Oaten et al, 2018; Royzman, Atanasov, Landy, Parks, & Gepty, 2014), which could potentially evoke a canonical disgust expression relatively independently of the judged severity of the behavior itself. This would be consistent with recent findings that reactions to classic purity violations are distinctively associated with disgust sensitivity (e.g., Tracy, Steckler, & Heltzel, 2019; Wagemans, Brandt, & Zeelenberg, 2018) but also with concerns about whether the classic purity domain violations are tapping into moral intuitions about behavior or other issues (Gray & Keeney, 2015; Kollareth & Russell, 2019; Royzman et al, 2014; Uhlmann & Zhu, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The lay meaning of the term "disgust" is indeed difficult to disentangle from "anger" or "contempt" (Herz & Hinds, 2013;Nabi, 2002;Piazza et al, 2018), and people likely use the term metaphorically to communicate their disapproval (Armstrong et al, 2020;Bloom, 2004;Nabi, 2002;Royzman & Sabini, 2001;Royzman & Kurzban, 2011). In line with this idea, pathogen-free violations of "spiritual purity" are not associated with the facial expression of disgust (Ritter et al, 2016); do not elicit a disgustrelated phenomenology (nausea, gagging, loss of appetite), nor action tendency (desire to move away) (Royzman et al, 2014); and are not associated with reporting being "grossed-out" (Kollareth & Russell, 2019) -the lay term more aptly capturing the cognitively strict sense of disgust (Herz & Hinds, 2013;Nabi, 2002). Second, disgust-based accounts of puritanism rely on the premise that simply perceiving an action as disgusting is sufficient to judge it immoral.…”
Section: Moral Foundations Theory and Disgust-based Accountsmentioning
confidence: 99%
“…In fact, in research that has directly tried to test whether moral violations without core disgust elicitors evoke the same emotion that core disgust elicitors do, individuals do not appear to experience the same sort of disgust as they do in response to pathogen threats. For instance, in a cross-cultural study, Kollareth and Russell (2019) created a variety of scenarios that described a moral purity violation or a non-purity moral violation, and which contained either a pathogen elicitor or not. They found that while the term "disgust" was used by both American and Indian participants when reporting responses to purity and non-purity moral violations, the term "grossed-out" (which captures the emotion of core disgust more accurately) was only used in reporting responses to pathogen violations.…”
Section: Criticisms Of the Extended Perspectivementioning
confidence: 99%
“…This, in turn, helps bolster the expanded view that disgust has become co-opted in the service of sociomoral regulation. More research is needed here, but to the extent that researchers have systematically separated pathogen-relevant content from these moral scenarios, it has become evident that disgust does not play the role predicted by the expanded account (e.g., Kollareth & Russell, 2019;Oaten et al, 2018).…”
Section: Pathogen-avoidance and Extended Perspectives On Disgust: Assessing The Evidencementioning
confidence: 99%